Variation Language Content Analysis Book (A Need Analysis Study) - Eva Nurul Chandra; Wiwik Yully Widyawati (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
This research aims to analyse whether the “Contrastive Linguistic and Error Analysis Book” is considered relevant to the SDGs criteria. The success of the English teaching learning process will also be encouraged by the application of instructional material. Most language programs rely heavily on teaching materials. Created material is one of the materials in a university. In this research, the writers used qualitative descriptive method. Then, the students who learned Contrastive Linguistics and Error Analysis (CLEA) and the lecturers who have taught CLEA were chosen to be the participants. The instruments used in this research were questionnaires both from student’s perspective and lecturer’s perspective. Student’s questionnaire consisted of 20 questions, and lecturer’s questionnaire consisted of 12 questions. The data collection was taken from 55 students and 8 lecturers who were given the questionnaire. Based on the results and discussion, it shows that dimension of “suit environment” from the lecturer’s perception, that the text in CLEA book is no longer suitable for this global era. Considering with Sustainable Development Goals, the CLEA textbook syllabus needs a revisiting to insert the SDGs theme in its reading text that is related with the 17 goals, such as: quality education, no poverty, zero hunger, gender equality, climate action, and many more. Since syllabus is guidance in achieving the learning objectives, it needs revisiting gradually to pursue the developing situation. The revisiting syllabus should consider both student and teacher as the practitioners of teaching and learning process. Hopefully by inserting the SDGs theme in the CLEA syllabus, student and teacher can be engaged together in creating a better life in the community.